Identifikasi Daerah Risiko Bencana Longsor di Kota Bogor: Identification of Landslide Risk in the City of Bogor - M. Galih Permadi; Boedi Tjahjono; Dwi Putro Tejo Baskoro (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2018)
Landslide is one of the disasters that often hit Indonesia. Data collected from BPBD Office of Bogor City also shows that landslide events ranked first out of 6 types of disasters in Bogor City; in 2017 there were 179 landslides (40.5%) of the 442 recorded disaster events. To support development programs in the city, landslide risk research is needed. This study aimed to assess and map the risk of landslides in Bogor City and formulate mitigation recommendations. The method used is the Multi Criteria Evaluation where the weights and scores of each parameter are obtained from the Analytical Hierarchy Process (AHP). The results obtained show that the highest level of susceptibility and landslide hazard is in the South Bogor District, this is in accordance with the landform conditions in the region, where 60.5% of the area has landforms with steep slopes i.e. denudational volcanic cones, river banks, and valleys with alluvial terrace. However, for the highest risk, the extent area is located in North Bogor District. This is due to the dominance of residential and high population, so the vulnerability factor is an indicator of rising risk values. For Bogor City which is dominant with residential, recommended mitigation include 3 types of engineering, namely civil, vegetative, and social for medium and high risk classes. Bogor Selatan sub-district in this case is the district with the most extensive area to implement mitigation measures.